Analisis Daya Dukung dan Kesesuaian Lingkungan Untuk Pengembangan Pariwisata Berkelanjutan di Pantai Lovina Buleleng, Bali - Kusumawati, Ni Putu Diah; Restu, I Wayan; Wijayanti, Ni Putu Putri (Bumi Lestari; Vol 23 No 1 (2023)DO - 10.24843/blje.2023.v23.i01.p05, 2023)
Lovina Beach is one of the tourist attraction located in Kalibukbuk Village, Buleleng District, Buleleng Regency, Bali. Lovina Beach has coastal waters that are still very natural so that it has the potential to be used as an ecotourism area. Information regarding the carrying capacity and environmental suitability for the development of sustainable tourism in Lovina Beach has not been carried out. This study aims to determine the environmental conditions and carrying capacity, and the condition of tourist objects on Lovina Beach for the development of sustainable tourism. Data collection was carried out in January-February the a quantitative and qualitative descriptive method. Observations and measurements were carried out at three stations with different characteristics of the aquatic environment. The condition of the tourist attraction on Lovina Beach is still very natural with a very attractive beauty charm and is supported by other supporting service facilities. The condition of the tourism suitability index for the beach recreation category is included in the category according to the value of 2,4 at stations 1 and 2, and the category is very in accordance with the value of 2,7 at station 3, while the carrying capacity of the area is obtained with a value of 2.291 people/day. The direction of developing tourist areas is to promote through social media and improve infrastructure at Lovina Beach. Keywords: carrying capacity; tourism suitability index; Lovina Beach